Крымская научная сессия АН СССР 1952 года и развитие крымоведения в середине ХХ века - Ломакин, Д.А. (Питання історії науки і техніки, 2009)
У статті розкрито й проаналізовано основні питання, розглянуті на засіданнях
об'єднаної наукової сесії Відділення історії й філософії АН СРСР і Кримської філії АН,
також висвітлена роль і вплив сесії на подальший розвиток кримознавства й історичної науки в цілому. This article is devoted to the analysis of the basic questions, which have been considered
at the sessions of the incorporated scientific session of the Branch of history and philosophy of
the Academy of sciences of the USSR and the Crimean branch of the Academy of sciences, and
its role and influence in further development of historical science in whole and crimean history
in particular.